Validity and reliability of the Thai 3-Minute Diagnostic Interview for CAM-defined Delirium (Thai 3D-CAM) - Thipakorn, Yanin; Thisayakorn, Paul (Chulalongkorn Medical Journal, 2021)
Background: Delirium is a common complication of hospitalized patients leading to worse outcomes. Screening tools can improve detection and prompt treatment. The 3-minute Diagnostic Interview for Confusion Assessment Method (CAM)-defined Delirium (3D-CAM) is a practical, valid, and reliable screening tool developed by Dr. Edward R. Marcantonio in 2014. The 3D-CAM was translated into Thai language. Objective: To demonstrate the validity and reliability of the Thai 3D-CAM compared to psychiatrist diagnosis based on the Diagnostic and Statistical Manual of Mental Disorders, Fifth edition (DSM-5). Methods: One hundred and forty-two patients were recruited with consent from the patients or a caregiver from adult inpatients requiring psychiatric consultation. Patients were assessed with the Thai 3D-CAM, the Thai Delirium Rating Scale-Revised-98 (DRS-R-98), followed by a psychiatric interview based on the DSM-5. Results: Delirium proportion in the study population was 48.6%. The most common motor subtype was mixed delirium (56.5%), followed by hyperactive (23.2%), and hypoactive delirium (20.3%). The sensitivity of the Thai 3DCAM was 91.3% (95% CI = 84.7 - 98.0), and specificity was 90.4% (95% CI = 83.6 - 97.2). Thai 3D-CAM results correlated with gold standard diagnosis, with X2 of 94.763 (P < 0.001), and Cohen’s kappa of 0.817 (95% CI = 0.723 - 0.911, P < 0.001). Internal consistency was demonstrated with Cronbach’s alpha = 0.708. Inter-rater reliability showed near perfect agreement (Kappa = 0.818, 95% CI = 0.577 - 1.059, P < 0.001). Conclusion: The Thai 3D-CAM is a valid and reliable screening tool for delirium. Availability of this screening tool could assist in improving detection and early treatment.